Dietery and Compliance of Iron Tablet Factors with the Incidence of Anemia in Pregnant Women - Wini, Thereza Aprilianti Du'a; Laga Nur, Marselinus; Landi, Soleman (Timorese Journal of Public Health, 2021)
Anemia is a condition of hb levels less than normal, which is 11.5 gr / dl. In 2018, there were 9531 cases of pregnant women, of which 2207 (23%) people suffered from anemia. Specifically for the Sikumana Health Center there are 523 cases. This study aims to see the relationship between diet and compliance with the consumption of Blood Added Tablets (TTD) with the incidence of anemia in pregnant women in the Sikumana Health Center work area in 2020. This research is quantitative research with a cross sectional approach. The study sample amounted to 70 people. The data was analyzed using the Chi Square test at a meaningful level of α=0.05. The results showed that there are two variables associated with the incidence of anemia in pregnant women, namely the type of eating (p-value = 0.000) the level of energy adequacy (p-value = 0.000), and adherence to the consumption of blood-added tablets (TTD) (p-value = 0.044). Variables that have no association with the incidence of anemia of pregnant women are the frequency of eating (p-value = 0.012). Pregnant women are expected to have a more active role in seeking information about balanced nutrition, namely the type of food and the level of energy adequacy needed during pregnancy as well as the rules for taking blood-added tablets to prevent anemia during pregnancy